ESTUDO DAS OXIDAÇÕES DO METANOL E DO ETANOL SOBRE ELETROCATALISADORES BINÁRIOS E TERNÁRIOS À BASE DE PLATINA, RÓDIO E MOLIBDÊNIO - Soares, Geasi Pavão (2011)
Study of oxidation of methanol and ethanol in acid medium, binary and ternary electrocatalysts based on platinum, rhodium and molybdenum supported on high surface area carbon prepared by alcohol reduction method. Was performed through the electrochemical techniques of cyclic voltammetry and chronoamperometry. The catalysts were characterized using transmission electron microscopy (TEM) and X-ray Diffraction (XRD). The results of TEM and XRD showed that the alcohol reduction method was very effective in the synthesis of catalysts, which are formed on the alloy series PtRh/C, and there is no alloying of the series PtMo/C. In the series PtRhMo / C can not be said whether or not formation of the league. The results of cyclic voltammetry and chronoamperometry showed that among the binary and ternary catalysts studied, PtRhMo/C (50:25:25) and PtRhMo/C (50:37,5:12,5) showed the best profile on the reactions of oxidation of ethanol and methanol, respectively.